Regional Economic Integration and Impacts on Growth, Poverty and Income Distribution - The Case of Vietnam - Nguyen, Tien Dung (ĐHKT, 2016)
Regional economic integration in East Asia has envolved in fact on the basic of market forces but, now in the 21st century, it is instituationally promoted by forming free trade agreements between countries in the region. Focusing on the network of FTAs in East Asia consist of ASEAN. This paper is based on the analysis of comparative statics for the benchmark year 2001.